Medical and social consequences of fractures of the proximal femur in elderly and senile subjects (literature review) - Babalyan, Vladimir; Hurbanova, Tamara; Cherepov, Dmytro; Khvysyuk, Оlexander; Kalchenko, Andrii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">The medico-social consequences of fractures of the proximal femur in elderly patients, the medical care system for such injuries in various countries, complications and lethality are analyzed. It was noted that the mortality rates during the first year after the fracture of proximal femur ranges from 21.5 to 40.0 %, in 20–50 % of cases, patients become disabled and even three years after injury the indicators of «physical functioning» and «general health» remain low. Return to the regular way of life fracture of proximal femur, observes in 20–50 % of patients only. It is established that 20–60 % of the injured persons need daily assistance, and more elderly people living in boarding schools and nursing homes, compared to those living in families. Based on the results of the STOP study (system for recording of osteoporotic fractures), Ukraine is classified as a country with a moderate risk of developing osteoporosis and its complications, and the incidence of fractures of proximal femur is similar to that of Romania and Poland. In Sweden and the UK, national programs have been developed for the treatment of patients with fracture of proximal femur, which include surgical intervention within 48 hours after trauma, geriatric consultation within 72 hours after admission, early post-operative mobilization, bedsore prevention, osteoporosis medication, supervision of a geriatrician. All this allowed to reduce the length of stay of the patient in the hospital, to reduce the number of complications, to reduce the lethality and the cost of treatment by 40 %. Surgical treatment of elderly and senile patients with proximal femur fractures as soon as possible is the «gold standard».